Causes of and risk factors for posttraumatic stress disorder: the beliefs of Iraqi and Afghan refugees resettled in Australia. Issue 1 (December 2017) - Slewa-Younan, Shameran; Guajardo, Maria; Yaser, Anisa; Mond, Jonathan; Smith, Mitchell; Milosevic, Diana; Smith, Caroline; Lujic, Sanja; Jorm, Anthony
Abstract Background Resettled refugees are a vulnerable group for mental health problems and in particular, trauma-related disorders. Evidence suggests that poor 'mental health literacy' (MHL) is a major factor in low or inappropriate treatment-seeking among individuals with mental health problems. This study sought to determine the beliefs regarding the causes of and risk factors for post-traumatic stress disorder (PTSD) amongst two resettled refugee groups in Australia. Methods Utilising a culturally adapted MHL survey method, 225 Iraqis and 150 Afghans of refugee background were surveyed. Results Approximately 52% of the Iraqi participants selected 'experiencing a traumatic event' as the 'most likely' cause for the clinical vignette, whereas 31.3% of the Afghan sample selected 'coming from a war torn country' as their top cause. While both groups identified being 'born in war torn country' as the most likely risk, at 34.4 and 48% of the Iraqis and Afghans respectively, differences regarding other risk factors selected were noted. Conclusions The results of this study indicate the need for culturally sensitive health promotion and early intervention programs seeking to improve MHL relating to PTSD in resettled refugee populations. There is also a need for mental health services to recognise that variation in MHL may be a function of both the cultural origin of a refugee population and their resettlement experiences. Such recognition is needed in order to bridge the gap between Western, biomedical models for mental health care and the knowledge and beliefs of resettled refugee populations.